Sacubitril/valsartan and circulating neprilysin hypothesis in patients with HFpEF. (25th November 2020) - Santiago-Vacas, E; Codina, P; Domingo, M; De Antonio, M; Zamora, E; Santesmases, J; Julian, M.T; Diez-Quevedo, C; Troya, M.I; Boldo, M; Altimir, S; Nunez, J; et al.
Abstract: Background: Neprilysin serum levels (sNEP) exhibited significant prognostic value in patients with heart failure (HF). In the PARADIGM-HF study benefit of sacubitril/valsartan was observed in patients with reduced ejection fraction (HFrEF), while in the PARAGON-HF benefit was only observed in the subgroup of patients with LVEF <57%. Objective: To assess the prognostic value of sNEP in ambulatory patients with HF and preserved ejection fraction (HFpEF) and LVEF >57% (group 1), in comparison with patients with LVEF ≤57% (group 2). Methods: Consecutive patients with HF attended at the Unit from May 2006 to February 2016 were considered for the study. The primary end-point was the composite of cardiovascular death or HF hospitalization. All-cause death, cardiovascular death, HF hospitalization and the composite of all-cause death or HF hospitalization were secondary end-points. Competing risk methods (R package by Bob Gray for SPSS) were used when required. Results: sNEP was measured in 1428 patients (age 67.7±12.7, 70.3% men, LVEF 35.8% ±14, 48.9% from ischemic etiology), 144 of which had a LVEF >57% (age 70.1±15, 43.8% men, 53.5% from hypertensive or valvular etiologies). sNEP levels did not significantly differ between the two groups of patients (p=0.31). During a mean follow-up of 6±3.9 years, 856 deaths were recorded (459 from cardiovascular causes) and 523 patients suffered at least one HF hospitalization. The primary end-point occurred in 941 patients (in 111 of the 144 patients with LVEF >57%). Table 1 shows sNEP age- and sex-adjusted hazard ratios for the primary and secondary end-points. Conclusions: sNEP prognostic value in patients with HFpEF and LVEF >57% outperforms that observed in patients with lower LVEF. These data support the personalized use of sNEP in identifying HFpEF patients that may benefit from treatment with sacubitril/valsartan. Funding Acknowledgement: Type of funding source: None